Measurements of electric charge separated during the formation of rime by the accretion of supercooled droplets - Lighezzolo, Rafael Andres (2010)
In these experiments, the electric charge carried by single particles ejected from the surface of a graupel particle growing by riming was measured. Simulated graupel pellets were grown by accretion of supercooled water drops, at temperatures ranging from-2 to-10 °C in a wind tunnel at air velocities between 5 and 10 m s-1, with the goal of studying the charging of graupel pellets under conditions of secondary ice crystal production (Hallett-Mossop mechanism). The graupel, and induction rings upstream and downstream of the graupel, were connected to electrometers and analyzing circuits of sufficient sensitivity and speed to measure, correlate and display individual charging events. The results suggest that fewer than 1% of the ejected particles carry a measurable electric charge (>2 fC). Further, it was observed that the graupel pellets acquire a positive charge and the average charge of a single splinter ejected is −14 fC. This mechanism of ejection of charged particles seems adequate to account for a positive charge of around 1 pC that individual precipitation particles ofmm- size could acquire in the lower part of the cloud, which in turn could contribute to the lower positive charge region of thunderstorms.